Znaczenie Turcji dla gospodarki i bezpieczeństwa Unii Europejskiej - Pohl, Artur (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
In the second decade of 21st century the European Union will have to face the economic crisis and a problem of its domestic and international security enhancement. In both cases, the Turkish access to the organization can be a cure for European problems. Fast-growing economy, with young, well-educated society as well as big market may be an impulse to the economic growth of the EU. Economic surroundings and geostrategic location of Turkey, with its strong and modern army, can positively affect the security of the organization.